INTERSTITIAL LUNG DISEASE IN A PREMATURE BABY - Елена Александровна Сидорова; Светлана Викторовна Цигельник; Наталья Владимировна Солдатова; Светлана Ивановна Елгина; Вадим Гельевич Мозес; Елена Владимировна Рудаева; Кира Борисовна Мозес (The Publishing House Medicine and Enlightenment, 2022)
Interstitial lung diseases (ISL), synonyms: diffuse lung diseases, diffuse parenchymal lung diseases, are a heterogeneous group of diseases in which alveoli and perialveolar interstitium are primarily involved in the pathological process, which leads to a violation of gas exchange, restretive violations of lung ventilation function and diffuse interstitial changes detected by X-ray examination. ISL is a rare pathology. It is believed that their true frequency is very difficult to determine, since due to the complexity of diagnosis, many cases remain unrecognized. Currently, it is believed that interstitial lung diseases occur at any age, but in children, they manifest in at least half of cases in the neonatal period or at the age of two years of life. In children under the age of one year, 2/3 of cases are due to diseases mainly occurring in the neonatal period. Submitted to а clinical case of a premature newborn girl with ISL diagnosed at the age of 1 month 11 days is presented. This clinical case indicates that it is necessary to work out the mechanism of making a decision to include interstitial lung diseases in the differential diagnostic search at an earlier stage.